2017
DOI: 10.1061/(asce)hy.1943-7900.0001389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lateral and Vertical Constrictions on Flow in Rough Steep Channels with Bedload

Abstract: Two-phase flows occurring at flow constrictions such as bridges or open sediment check dams are complex, especially for steep rivers with bedload transport. Dangerous bedload deposition and backwater effects may occur in steep mountain rivers at bridges. In contrast, sediment deposition is desirable at open check dams combined with sediment traps. For design purposes, the discharge and bedload capacity across these flow constrictions must be known. The energy losses, discharge capacity, and bedload transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Sci. Previous studies have shown that the retention of bed load is hydraulically initiated as soon as the barrier causes a hydraulic jump upstream underlying generally supercritical flow conditions (Schwindt et al, 2017a(Schwindt et al, , 2017b. Supercritical flow conditions are typical in mountain rivers but not omnipresent (e.g., Heyman et al, 2016).…”
Section: Design Approach For Permeable Sediment Traps 25mentioning
confidence: 99%
See 4 more Smart Citations
“…Sci. Previous studies have shown that the retention of bed load is hydraulically initiated as soon as the barrier causes a hydraulic jump upstream underlying generally supercritical flow conditions (Schwindt et al, 2017a(Schwindt et al, , 2017b. Supercritical flow conditions are typical in mountain rivers but not omnipresent (e.g., Heyman et al, 2016).…”
Section: Design Approach For Permeable Sediment Traps 25mentioning
confidence: 99%
“…Therefore, the experimental set-up (as used by the authors in Schwindt et al, 2017a;2017b) included a widened deposition area, according to typical sediment traps in a mountain-river-like environment.…”
Section: Sediment Deposition Processes and Controlsmentioning
confidence: 99%
See 3 more Smart Citations